2019
DOI: 10.1016/j.memsci.2019.04.060
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life RO membranes recycling: Reuse as NF membranes by polyelectrolyte layer-by-layer deposition

Abstract: Nowadays, end-of-life (EoL) reverse osmosis (RO) membranes are considered as waste, hence they are incinerated or discarded in landfills. Due to the environmental problem of disposed membranes, their reuse as nanofiltration (NF) membranes was studied in this study. At first, the fouling of EoL membrane was cleaned and then the effect of sodium hypochlorite (NaOCl) on removing the polyamide (PA) layer and pure water permeability (PWP) of EoL membranes was investigated. With regard to NaOCl exposure intensities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Environmental engineers and material scientists have attempted downcycling end-of-life high pressure reverse osmosis/nanofiltration (RO/NF) membranes into NF/ultrafiltration (UF) membranes after appropriate treatment (Fig. 1A) (12,13). Nevertheless, for fouled/end-of-life low pressure membranes (MF/UF), how to recycle these membranes in a cost-effective and technically feasible way remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental engineers and material scientists have attempted downcycling end-of-life high pressure reverse osmosis/nanofiltration (RO/NF) membranes into NF/ultrafiltration (UF) membranes after appropriate treatment (Fig. 1A) (12,13). Nevertheless, for fouled/end-of-life low pressure membranes (MF/UF), how to recycle these membranes in a cost-effective and technically feasible way remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…This type of RO membrane was recycled using PA oxidizing agents such as sodium hypochlorite (NaOCl) to fully or partially degrade the PA layer responsible of irreversible fouling [ 8 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. By applying different exposure doses to the oxidizing agent, quantified by units of parts per million of NaOCl used in the cleaning solution multiplied by the exposure time in hours (ppm·h), discarded RO membranes have been transformed to membranes for microfiltration (MF), ultrafiltration (UF) or nanofiltration (NF) separation processes [ 10 , 13 , 15 , 16 , 17 , 18 , 23 ]. In other research studies, after exposing the RO modules to NaClO oxidizing aqueous solution, the membranes were transformed to anion or cation exchanged membranes for electrodialysis (ED) or to microsystin-degrading biofilms for membrane bioreactors by applying adequate approaches [ 19 , 20 , 21 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a process is reported that allows for the recycling of spent membranes taken from seawater desalination plants or similar plants and their reuse them as microfiltration or ultrafiltration membranes. The recycling is based on the removal of both the fouling and active layers of spent membrane using a suitable stripper to avoid damaging the microporous layer of the membrane [16]. The regenerated membrane was subjected to clarification of a WPPA to access its performance in terms of flux and rejection of suspended particles and organic matter.…”
Section: Introductionmentioning
confidence: 99%